Alteration of the steroidogenesis in boys with autism spectrum disorders - Janšáková, Katarína; Hill, Martin; Čelárová, Diana; Celušáková, Hana; Repiská, Gabriela; Bičíková, Marie; Máčová, Ludmila; Ostatníková, Daniela (Translational psychiatry, 2020)
The etiology of autism spectrum disorders (ASD) remains unknown, but associations between prenatal hormonal changes and ASD risk were found. The consequences of these changes on the steroidogenesis during a postnatal development are not yet well known. The aim of this study was to analyze the steroid metabolic pathway in prepubertal ASD and neurotypical boys. Plasma samples were collected from 62 prepubertal ASD boys and 24 age and sex-matched controls (CTRL). Eighty-two biomarkers of steroidogenesis were detected using gas-chromatography tandem-mass spectrometry. We observed changes across the whole alternative backdoor pathway of androgens synthesis toward lower level in ASD group. Our data indicate suppressed production of pregnenolone sulfate at augmented activities of CYP17A1 and SULT2A1 and reduced HSD3B2 activity in ASD group which is partly consistent with the results reported in older children, in whom the adrenal zona reticularis significantly influences the steroid levels. Furthermore, we detected the suppressed activity of CYP7B1 enzyme readily metabolizing the precursors of sex hormones on one hand but increased anti-glucocorticoid effect of 7α-hydroxy-DHEA via competition with cortisone for HSD11B1 on the other. The multivariate model found significant correlations between behavioral indices and circulating steroids. From dependent variables, the best correlation was found for the social interaction (28.5%). Observed changes give a space for their utilization as biomarkers while reveal the etiopathogenesis of ASD. The aforementioned data indicate a direction of the future research with a focus on the expression and functioning of genes associated with important steroidogenic enzymes in ASD patients from early childhood to adrenarche.
Keywords: poruchy autistického spektra; Pregnancy; Humans; Case-Control Studies; dítě; studie případů a kontrol; Child; Autism Spectrum Disorder; Female; lidé; Biomarkers; steroidy; předškolní dítě; biologické markery; ženské pohlaví; Male; těhotenství; mužské pohlaví; Child, Preschool; Steroids